Uji Toksisitas Akut Ekstrak Buah Bruguiera gymnorrhiza pada Tikus (Rattus norvegicus) (Acute Toxicity Test of Bruguiera gymnorrhiza Fruit Extract In Rats (Rattus norvegicus)) - Salman Al Farisi; Al Munawir; Zahrah Febianti (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Bruguiera gymnorrhiza (bakau) fruit has a great potency as a traditional medicine, but the safety has not known yet, therefore a test to determine the toxic effects of this fruit into living thing is needed. This research aimed to determine the acute toxicity effect of Bruguiera gymnorrhiza fruit extracts in rats based on Loomis criteria. This research was an experimental research laboratory with Post Test Only Control Group Design. Ten rats were divided into two groups. The control group was fed with a standard food while the treatment group was given Bruguiera gymnorrhiza (bakau) fruit extract at a dose of 5.000 mg/kg BB. After 24 hours, two groups were observed by calculating the number of the dead rats, if there was no dead rat, they were sacrificed for an autopsy for liver histopathological examination. The result of this research showed there was no dead rat during the treatment process . Histopathological examination of rat liver cells showed no necrosis, degeneration, inflammation, fibrosis, and cirrhosis. Conclusion of this research was Bruguiera gymnorrhiza (bakau) fruit had no toxic effects and could be clasified as “Practical Not Toxic” in Loomis criteria . Keywords: Bruguierra gymnorrhiza (bakau) fruit , the acute toxicity effect, rat